Composition, community structure, and vertical distribution of epiphytic ferns on Cyathea junghuhniana in Gede-Pangrango National Park, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hasanah U, Hadisunarso, Praptosuwiryo TN. 2021. Composition, community structure, and vertical distribution of epiphytic ferns on Cyathea junghuhniana in Gede-Pangrango National Park, Indonesia. Biodiversitas 22: 4968-4976. Epiphytic ferns are a significant component of tropical forests worldwide and contribute significantly to the high species diversity found in tropical regions. Tree ferns are important phorophytes for the establishment and occurrence of epiphytic fern species in tropical forests. The first detailed description of the diversity and abundance of epiphytic ferns on the tree fern Cyathea junghuhniana (Kunze) Copel.  in a natural forest of Indonesia is provided. This study aimed to determine the species composition, richness, abundance, community structure, and vertical distribution of epiphytic ferns growing on the tree fern C.  junghuhniana in the mountain forest of Gede-Pangrango National Park, West Java, Indonesia. The 35 tree fern caudices of at least 3 m height were selected by purposive random sampling. Each tree fern was divided into intervals of 1 meter from ground level to a height of three meters, thus obtaining 105 one-meter samples of the epiphytic fern community on tree fern caudices stratified according to height. The Importance Value Index (IVI) was estimated for each species of epiphyte based on the frequency of occurrence on caudices. The 35 tree fern caudices hosted 760 fern epiphytes belonging to 12 species of 9 genera and 6  families. The highest species richness occurred in Polypodiaceae. The species with the highest Importance Value Index (IVI = 1.24 %) was Nephrolepis davallioides (Sw.) Kunze, with increasing frequency from bottom to top of the caudex.
Keywords: Cyathea junghuhniana, tree fern phorophyte, species richness, wet tropical forest